IMPLEMENTASI NILAI-NILAI MODERASI BERAGAMA DALAM PROGRAM PPI (PETA PERTUMBUHAN INDIVIDU) DI MI MA’HAD ISLAMY YOGYAKARTA - Difaul Husna; 'Aabidah Ummu 'Aziizah; Sangkot Sirait (STAI Ma'had Aly Al-Hikam Malang, 2023)
Religious moderation in educational practices at Madrasah Ibtidaiyyah is often only understood in the context of interactions between religious communities (external religious moderation), so it does not contribute much to students' understanding of the concept of religious moderation in the internal sphere which students usually encounter in homogeneous schools such as madrasas, schools private Muhammadiyah, Integrated Islamic Elementary School (SDIT) and the like as the main characteristic of a Muslim. While religious moderation is a noble value that needs to be habituated through a reciprocal social approach (reciprocity) between schools and students as well as parents and guardians and vice versa. This study took research locations at the Ibtidaiyyah Ma'had Islamy Yogyakarta Madrasah grades I and II as a representation of homogeneous elementary schools with the implementation of the Individual Growth Map program. The data is processed using two data analysis concepts, (1) scientific data analysis, which is returned to the previous theoretical framework, namely Alvin W. Gouldner's Reciprocal theory (2) methodological data analysis, namely technical research carried out by Miles and Huberman, with details of reduction, presentation data, conclusion, and verification. The results of the research are in the form of strategies and the discovery of religious moderation values contained in the PPI MI Ma'had Islamy Yogyakarta program in class I and class II.